2021
DOI: 10.1146/annurev-immunol-101819-074948
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells: From Innate to Adaptive Features

Abstract: Natural killer (NK) cells are innate lymphocytes that provide critical host defense against pathogens and cancer. Originally heralded for their early and rapid effector activity, NK cells have been recognized over the last decade for their ability to undergo adaptive immune processes, including antigen-driven clonal expansion and generation of long-lived memory. This review presents an overview of how NK cells lithely partake in both innate and adaptive responses and how this versatility is manifest in human N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 224 publications
2
86
0
Order By: Relevance
“…NK cells are the third largest lymphocyte population and play an important role in innate immunity by eliminating transformed cells and virus-infected cells. Recent studies, including ours, confirmed the role of NK cells in the regulation of adaptive immunity through expression of immunoregulatory cytokines, including IFN-γ [ 37 , 38 ]. Human NK cells also express IL-24 with mitogen stimulation [ 16 ].…”
Section: Immunobiology Of Il-24supporting
confidence: 54%
“…NK cells are the third largest lymphocyte population and play an important role in innate immunity by eliminating transformed cells and virus-infected cells. Recent studies, including ours, confirmed the role of NK cells in the regulation of adaptive immunity through expression of immunoregulatory cytokines, including IFN-γ [ 37 , 38 ]. Human NK cells also express IL-24 with mitogen stimulation [ 16 ].…”
Section: Immunobiology Of Il-24supporting
confidence: 54%
“…Cytokine regulation comprises the third signal for T-cell activation and differentiation, and also plays a crucial role for NK cell development, differentiation, and effector function. 151 But unlike T cells, NK cells can respond robustly to many cytokines without the requirement of activating-receptor signaling, highlighting the traditional innate function of NK cells. As such, these cytokines are being exploited in the clinic to enhance NK cell cellular therapy.…”
Section: Cytokine Regulation (Signal 3)mentioning
confidence: 99%
“…Direct evidence for a CMV-induced imprint of the NK cell compartment was obtained in in vivo studies showing that long-lived Ly49H positive NK cells, that were able to mount recall responses, preferentially expanded in mice upon MCMV infection (147). Moreover, in vitro studies showed that CMV-infected cells induce proliferation of NKG2C brigth NK cells (148) although the molecular basis has not been fully resolved, interaction with HLA-E presenting CMV derived peptides is one of the main mechanisms suggested to drive the response (149,150).…”
Section: Non-classical Hla Class I Molecules As Ligands For Nk Cell Receptors In Kidney Transplantationmentioning
confidence: 99%